The Effect of Brand Reputation, Service Quality, and Price Perception on Consumer Satisfaction at The Sutejo Motorcycle Spare Parts Store in Nganjuk - Putra, Aldafa Tito Ramanda; Kusumaningtyas, Dian (Universitas Nusantara PGRI Kediri, 2025)
Research aim: The purpose of this study is to analyze the influence of brand reputation, service quality, and price perception on consumer satisfaction at the Sutejo Nganjuk Motorcycle Spare Parts Shop. Design/Method/Approach: This study employed a quantitative approach with a causality method. The sampling technique used mixed sampling with an accidental sampling method, involving 40 active consumers of the Sutejo Motorcycle Spare Parts Store. Data analysis was conducted using classical assumption tests, multiple linear regression, and hypothesis testing (t-test and F-test). Research Findings: The results of the study indicate that partially, service quality and price perception have a significant positive effect on customer satisfaction, with price perception being the most dominant factor. Conversely, brand reputation has a negative effect when it does not meet consumer expectations. Simultaneously, brand reputation, service quality, and price perception significantly influence customer satisfaction. Theoretical contribution/Originality: This study integrates brand reputation, service quality, and price perception factors in influencing consumer satisfaction, providing new insights regarding the combination of these variables in the context of spare parts retail in Indonesia. Practitionel/Policy implications: The research results provide recommendations for Sutejo Motorcycle Spare Parts Store to improve its brand reputation through appropriate branding strategies, improve service quality through staff training, and adjust its pricing strategy to align with consumer value perceptions. These steps can increase customer satisfaction and loyalty. Research limitations: This study only examined three variables, while other factors such as promotions, customer experience, and product quality could potentially influence consumer satisfaction. Further research could expand the scope of variables for more comprehensive results.